Pengaruh Pertumbuhan Ekonomi, Tingkat Inflasi dan Nilai Tukar Rupiah Terhadap Penerimaan Pajak di Indonesia - Manisha Pratiwi; Emi Masyitah (ProBisnis : Jurnal Manajemen, 2025)
This study aims to examine and analyze the effect of economic growth, inflation rate, and the rupiah exchange rate on tax revenue in Indonesia during the 2021–2023 period. This research is a quantitative study with an associative type, using secondary data obtained from the Central Bureau of Statistics (BPS) and the Directorate General of Taxes (DJP). The data analysis techniques used in this study are multiple linear regression, classical assumption tests, t-test, F-test, and the coefficient of determination (R²), assisted by SPSS software. The results of this study indicate that partially, economic growth and the rupiah exchange rate have a significant effect on tax revenue, while the inflation rate does not. However, simultaneously, the three independent variables do not have a significant effect on tax revenue in Indonesia. The coefficient of determination (R²) of 0.882 shows that 88.2% of the variation in tax revenue can be explained by the three variables, while the remaining 11.8% is explained by other factors outside this study.